Closing policy gaps to enable agripreneurship of smallholder farmers in developing countries - Raymond Saner; Lichia Yiu; Shaun Roberts (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
This study investigates the broader context of smallholder farmers' operations and provides insights into the options that smallholder farmers in poor developing countries have when engaging in agripreneurial undertakings for additional income generation. Such personal agency when effective could support them to alleviate poverty, reduce hunger, and attain sustainable livelihood. Yet in practice, such personal efforts are often wrought with uncertain outcomes. Therefore an enabling policy environment is necessary to ensure the success of this strategic intervention in lifting and supporting sustainable livelihoods of rural farmers struggling with the precarity of their life situation.
Keywords: 330